Concession model for fair distribution of benefits and risks in build-operate-transfer road projects - Yan, Xue; Chong, Heap-Yih; Zhou, Jing; Li, Qian (Journal of Civil Engineering and Management, 2019)
A fair distribution of benefits and risks is not only one of the key factors in deciding concession period but also an important prerequisite for good cooperation between the government and the private sector in a Build-Operate-Transfer (BOT) road project. Considering the psychological characteristic of decision makers’ fairness preference, this study innovatively introduces the inequity aversion theory into the concession model, which provides a novel perspective to investigate the distribution of benefits and risks. In the improved model, the decision makers’ investment utility involves their economic benefits as well as their disutility due to inequity. Furthermore, the equilibrium principle of benefits and risks in this model has changed to minimize the gap between the investment utility-risk ratios of the government and the private sector. Based on Monte Carlo simulation, this study verifies the application of the model to a BOT road project in China. The results show that the concession period with fairness preference can effectively narrow the gap between the investment utility-risk ratios of the government and the private sector, thus guaranteeing the fair distribution of benefits and risks in the BOT road project.